Cognitive Factors of Life Satisfaction among the Russian Elderly - Elena V. Belovol; Zlata V. Boyko; Elena Yu. Shurupova (Peoples' Friendship University of Russia (RUDN University), 2020)
The overall aim of this article was to examine factors related to life satisfaction in old age. There are several approaches to understanding life satisfaction in psychology. Some theories that emphasize objective circumstances as most influential for life satisfaction are commonly labelled bottom-up theories, whereas theories that focus on stable individual characteristics are commonly labelled top-down theories. It is argued that certain personality traits, in particular extraversion and neuroticism, partly determine a persons satisfaction with life. At the same time, cognitive factors related to life satisfaction are rarely the subject of empirical research. In this study, age, social status (works, does not work, in retirement), type of family (nuclear or extended), and a number of indices of cognitive functioning (cognitive flexibility, memory - short-term and long-term, creativity and thinking) were used as predictor variables of life satisfaction. Ninety-seven respondents aged 50-84 participated in the research, which finds that, along with non-cognitive factors of life satisfaction, cognitive factors play great roles as well. Based on the data obtained, an empirical model of cognitive factors of life satisfaction was constructed. This research demonstrates that all cognitive variables examined (flexibility of thinking, long-term memory, short-term memory, thinking and creativity) make positive contributions to increasing satisfaction; notably the roles of long-term memory and creativity are especially salient. This study also found satisfaction is significantly higher among working older respondents when compared with their non-working colleagues, with the oldest employees the most satisfied. Family status is a factor related to life satisfaction in old age as well, since old people who live with a spouse are more satisfied than those who live in extended families with children and grandchildren. A regression model combined variables from top-down and bottom-up theories. The model includes memory and age as personal characteristics, and family type as a circumstantial predictor for life satisfaction in old age.